Securing the City: Emerging Markets in the Private Provision of Security Services in Chicago - Theodore, Nikolas (Social justice, 2006)
Part of a special issue on resistance to neoliberal globalization. The private security industry in Chicago has capitalized on rising fears of insecurity to expand its reach into formerly public-sector domains, such as the policing of public space. The expansion of the private security industry, together with a growing reliance on advanced surveillance technology, has coincided with the ascendancy of order maintenance policing as the dominant orientation to securing public space. The privatization of security in Chicago's public transit system and public housing sector illustrate how the markets for private security services are constructed and highlight implications of the privatization of security for public safety in urban areas.